The Inhibitory Effect of Aspirin on Human Endothelial Cells - Nordoy, Arne; Svensson, Birgit; Schroeder, Connie; Hoak, John C (Thrombosis and Haemostasis, 1978)
Human endothelial cell monolayers prepared from umbilical veins have been incubated with aspirin (1–2 mM) dissolved in Hepes modified solution and in platelet-rich plasma. They have also been incubated with plasma prepared from subjects before and after intake of aspirin giving a mean plasma concentration of 0.5 mM. The effects of the endothelial cells on ADP and collagen-induced platelet aggregation and malondialdehyde production in platelet-rich plasma have been tested. The endothelial cells had a spontaneous inhibitory effect on all three parameters. This effect was abolished when the cells were incubated with aspirin dissolved in MHS for 20 min and the increase in effect observed when platelet-rich plasma was incubated with endothelial cells for a period of 30 min was similarly inhibited when aspirin was dissolved in plasma or when plasma prepared from subjects who had taken aspirin were used. Aspirin had no inhibitory effect on prostacyclin (PGI2) with regard to the effect of PGI2 on platelets. On the contrary, the two compounds had an additive inhibitory effect on platelet aggregation induced by ADP and collagen. These findings should be considered with regard to the use of aspirin as an antithrombotic agent.